Teachers’ Social-Emotional Readiness in Handling Children with Special Needs in Early Childhood Education at PAUD Cikal Insani - Nursiyam Triadnani; Arizka Harisa (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
This study aims to describe teachers’ social-emotional readiness in handling children with special needs (CSN) at PAUD Cikal Insani. A descriptive qualitative approach was employed, with data collected through observation and in-depth interviews with the main teacher. The findings indicate that inclusive learning at PAUD Cikal Insani is implemented in a single central classroom that accommodates both regular children and children with special needs. Teachers demonstrate strong social-emotional competencies, such as empathy, self-control, and patience when dealing with diverse child behaviors. The learning strategies applied are individualized and situational, tailored to each child’s specific needs. Despite limitations in facilities and the absence of specialized training related to handling children with special needs, teachers are still able to create an inclusive and supportive learning environment. These findings emphasize that teachers’ social-emotional readiness is a fundamental factor in the success of inclusive education at the early childhood level. Teachers with high emotional intelligence are capable of building positive relationships and optimally supporting children’s social development.